Mesenchymal stem cell‐derived extracellular vesicles suppress the fibroblast proliferation by downregulating FZD6 expression in fibroblasts via micrRNA‐29b‐3p in idiopathic pulmonary fibrosis. Issue 11 (17th June 2020) - Wan, Xuan; Chen, Shuyun; Fang, Yan; Zuo, Wei; Cui, Jian; Xie, Shiguang
Abstract: Idiopathic pulmonary fibrosis (IPF), a progressive and fatal lung disease, usually leads to an irreversible distortion of the pulmonary structure. The functional roles of bone marrow‐derived mesenchymal stem cells (BMSC)‐secreted extracellular vesicles (EVs) in fibroblasts have been implicated, yet their actions in the treatment of IPF are not fully understood. This study investigated the roles of BMSC‐derived EVs expressing miR‐29b‐3p in fibroblasts in IPF treatment. EVs derived from BMSCs were successfully isolated and could be internalized by pulmonary fibroblasts, and Cell Counting Kit‐8 (CCK‐8) and Transwell assay results identified that EVs inhibited the activation of fibroblast in IPF. miR‐29b‐3p, frizzled 6 (FZD6), α‐skeletal muscle actin (α‐SMA), and Collagen I expressions were examined, which revealed that miR‐29b‐3p was poorly expressed and FZD6, α‐SMA, and Collagen I were overexpressed in pulmonary tissues. Dual‐luciferase reporter assay results demonstrated that miR‐29b‐3p could inversely target FZD6 expression. The gain‐ and loss‐of‐function assays were conducted to determine regulatory effects of FZD6 and miR‐29b‐3p on IPF. CCK‐8 and Transwell assays results displayed that BMSCs‐derived EVs overexpressing miR‐29b‐3p contributed to inhibited pulmonary interstitial fibroblast proliferation, migration, invasion, and differentiation. Furthermore, the effects of BMSCs‐derived EVs overexpressing miR‐29b‐3p on IPF progression were assessed in vivo, which confirmed the repressive effects of BMSCs‐derived EVs overexpressing miR‐29b‐3p on IPF progression. Collectively, BMSCs‐derived EVs overexpressing miR‐29b‐3p relieve IPF through FZD6. Abstract : Mesenchymal stem cell (MSC)‐derived extracellular vesicles (EVs) containing microRNA‐29b‐3p (miR‐29b‐3p) inhibit the expression of Frizzled 6 (FZD6) in fibroblasts, thereby inhibiting fibroblast proliferation, migration, and differentiation towards myoblast, and improving idiopathic pulmonary fibrosis progression in vivo.